2011
DOI: 10.1186/1471-2164-12-185
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium botulinum group III: a group with dual identity shaped by plasmids, phages and mobile elements

Abstract: BackgroundClostridium botulinum strains can be divided into four physiological groups that are sufficiently diverged to be considered as separate species. Here we present the first complete genome of a C. botulinum strain from physiological group III, causing animal botulism. We also compare the sequence to three new draft genomes from the same physiological group.ResultsThe 2.77 Mb chromosome was highly conserved between the isolates and also closely related to that of C. novyi. However, the sequence was very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 42 publications
3
95
1
1
Order By: Relevance
“…Interestingly, the housekeeping gene sequences of C. botulinum C strain Eklund clustered within the branch containing C. novyi A, which is distantly related to the one containing the C. botulinum C strain, 468. These results are in agreement with those from the phylogenomic analysis of Skarin et al (16), which show that C. botulinum C strain Eklund is closely related to C. novyi A. The two C. botulinum C strains share 97.2% 16S rRNA gene sequence identity, suggesting that strain Eklund might be assigned to a different species.…”
supporting
confidence: 82%
“…Interestingly, the housekeeping gene sequences of C. botulinum C strain Eklund clustered within the branch containing C. novyi A, which is distantly related to the one containing the C. botulinum C strain, 468. These results are in agreement with those from the phylogenomic analysis of Skarin et al (16), which show that C. botulinum C strain Eklund is closely related to C. novyi A. The two C. botulinum C strains share 97.2% 16S rRNA gene sequence identity, suggesting that strain Eklund might be assigned to a different species.…”
supporting
confidence: 82%
“…15 Two additional draft genomes are also available in GenBank. The main conclusion drawn from analyzing the genome results is that group III strains are more influenced by the plasmids they possess than group I and II strains.…”
Section: Horizontal Gene Transfer Of Toxin Genes In Clostridium Botulmentioning
confidence: 99%
“…15 Included among them are elements related to the IS6, IS21, IS256, IS1182 and IS200/ IS605 families. Whereas mobile elements account for 3.4% of the genetic content of the BKT015925 chromosome, the density is highest on the two middle sized plasmids (p2BKT015925 and p3BKT015925) where IS elements constitute 8 and 12% respectively of the total genetic content.…”
Section: Horizontal Gene Transfer Of Toxin Genes In Clostridium Botulmentioning
confidence: 99%
“…17 Genes encoding BoNTs can be located on the chromosome or on extrachromosomal elements, such as plasmids or bacteriophages. [18][19][20] Specifically, toxin genes for group III organisms are carried by bacteriophages that exert an unstable lysogenic cycle. Molecular and genomic analysis of the bacteriophage genome revealed that this phage exists as a circular plasmid prophage in the lysogenic state, and it does not integrate into the host chromosome.…”
Section: Bont-producing Clostridia and Their Toxinsmentioning
confidence: 99%